Porous carbon material, preparation method and application

CN122739352BActive Publication Date: 2026-11-03JIANGSU KINGWILLS CARBON-BASED INNOVATIVE MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611191891.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-11-03
Estimated Expiration
2046-08-07

AI Technical Summary

Technical Problem

Existing silicon-carbon anode materials suffer from poor capacity utilization and severe cycle life degradation due to their high expansion rate and poor conductivity, which limits their application in lithium-ion secondary batteries.

Method used

The material is porous carbon. The core particles consist of a carbon skeleton with a porous structure and a first lithium salt filled in it. The surface is coated with a conductive layer containing nitrogen compounds. The lithium salt in the carbon skeleton provides a pre-stored lithium source, and the nitrogen compounds in the conductive layer enhance conductivity and nucleation induction ability.

Benefits of technology

It effectively suppresses the volume expansion of silicon-carbon anode materials, improves cycle performance and capacity, enhances first-time coulombic efficiency, and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122739352B_ABST
    Figure CN122739352B_ABST
Patent Text Reader

Abstract

The application discloses a porous carbon material, a preparation method and application, wherein the porous carbon material comprises a core particle and a conductive layer located on the surface of the core particle; the core particle comprises a carbon skeleton with a pore structure and a first lithium salt filled in the pore structure; and the conductive layer is distributed with a nitrogen-containing compound, which comprises at least one of an ammonium phosphate compound and an organic nitrogen compound. The first lithium salt in the core of the porous carbon material is filled in the pores of the carbon skeleton, a pre-stored lithium source is provided, active lithium consumed by SEI film formation is compensated in situ when the battery is charged for the first time, and the loss of the first effect is relieved; and the existence can also regulate the pore wettability and ion transmission path. The nitrogen-containing compound in the conductive layer can enhance the nucleation induction ability of subsequent CVD silicon deposition, and improve the intrinsic electronic conductivity of the conductive layer. Therefore, the porous carbon material in the application can take into account the cycle performance and capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon materials technology, and more specifically, to porous carbon materials, preparation methods, and applications. Background Technology

[0002] Lithium-ion rechargeable batteries are widely used in 3C (computers, communications, and consumer electronics), electric vehicles, and energy storage fields due to their high energy density, long cycle life, and economic and environmental friendliness. However, with continuous economic development, current lithium-ion batteries can no longer meet the ever-increasing demand for energy density. Developing high-specific-capacity anode materials is one of the main ways to improve battery energy density. Currently, the most widely discussed high-capacity anode material for lithium-ion rechargeable batteries is silicon-carbon anode material, as its specific capacity is much higher than that of traditional graphite anode materials, and it also boasts advantages such as abundant resources and environmental friendliness, making it one of the optimal choices for high-energy lithium-ion battery anode materials.

[0003] However, silicon-carbon anode materials suffer from poor capacity utilization and severe cycle life degradation due to their high expansion rate and poor conductivity. These factors limit their application in lithium-ion secondary batteries. Since the expansion rate and conductivity of silicon-carbon anode materials are closely related to the performance of the porous carbon that makes up the silicon-carbon material, a carbon material that can suppress the expansion of silicon-carbon anode materials and improve their conductivity has become a focus of attention.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] The purpose of this invention is to provide porous carbon materials, preparation methods and applications, which are beneficial for suppressing the volume expansion of silicon-carbon anode materials, improving cycle performance, and ensuring that they have high capacity.

[0006] This invention is implemented as follows: In a first aspect, the present invention provides a porous carbon material, comprising core particles and a conductive layer located on the surface of the core particles; The core particles comprise a carbon skeleton with a porous structure and a first lithium salt and / or decomposition products of the first lithium salt filling the porous structure. The conductive layer contains nitrogen-containing compounds and / or decomposition products of nitrogen-containing compounds, wherein the nitrogen-containing compounds include at least one of ammonium phosphate compounds and organic nitrogen compounds.

[0007] In an optional embodiment, the first lithium salt is selected from at least one of lithium hydroxide, lithium carbonate, lithium niobate, lithium oxalate, lithium chloride, lithium fluoride, lithium hydride, lithium nitride, lithium nitrate, and lithium aluminate. And / or, the mass ratio of lithium element to carbon skeleton derived from the first lithium salt is 0.1% to 3%; And / or, the nitrogen-containing compound is selected from at least one of melamine, triammonium phosphate, diammonium hydrogen phosphate, and diammonium dihydrogen phosphate; And / or, the mass ratio of nitrogen element in the nitrogen-containing compound to the mass of the core particle is 0.001%-0.005%; And / or, the carbon skeleton is coconut shell pyrolysis carbon; And / or, the carbon skeleton is a carbon material with a disordered structure; And / or, the carbon framework has a hierarchical pore distribution; And / or, the thickness of the conductive layer is 50-100 nm; And / or, the conductive layer includes a highly conductive material selected from at least one of pitch carbon, mesophase carbon microspheres, soft carbon, hard carbon, petroleum coke, carbon fiber, resin pyrolysis carbon, acetone pyrolysis carbon, alkane pyrolysis carbon, olefin pyrolysis carbon, and acetylene pyrolysis carbon. And / or, the conductive layer further includes a conductive agent and / or a second lithium salt.

[0008] In an optional embodiment, the mass ratio of the highly conductive material to the nitrogen element in the nitrogen-containing compound in the conductive layer is 1:0.1-0.4; And / or, in the conductive layer, the mass ratio of highly conductive material to conductive agent is 1:0.5-0.7; And / or, in the conductive layer, the mass ratio of the highly conductive material to the lithium element derived from the second lithium salt is 1:0.1-0.5; And / or, the conductive agent is selected from at least one of conductive carbon black, super conductive carbon, Ketjen black, carbon nanotubes, graphene and acetylene black; And / or, the second lithium salt is selected from at least one of lithium bis(trifluoromethyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium carbonate, lithium hydroxide, lithium fluoride, and lithium hydride.

[0009] In an optional embodiment, the micropore volume in the carbon framework accounts for 35% to 90% of the total pore volume; And / or, the total pore volume of the carbon framework is 0.85cc / g to 1.2cc / g; And / or, the particle size D50 of the carbon skeleton is 3-15 μm.

[0010] Secondly, the present invention provides a method for preparing the porous carbon material according to any one of the foregoing embodiments, comprising: The first lithium salt is filled into the pores of the carbon framework to obtain the core particles; The core particles are coated with a mixture of highly conductive materials and nitrogen-containing compounds, and then the resulting coating material is passivated to obtain the porous carbon material.

[0011] In an optional embodiment, the preparation of the carbon skeleton is also included: the biomass powder is sequentially carbonized and etched to obtain the carbon skeleton; And / or, the filling of the first lithium salt includes uniformly mixing the first lithium salt with a carbon skeleton and then sintering it to obtain the core particles; And / or, coating includes uniformly mixing the mixture with the core particles, followed by passivation; And / or, the mixture further includes a conductive agent and / or a second lithium salt; And / or, the biomass is selected from at least one of tall coconut shells, dwarf coconut shells, and hybrid coconut shells.

[0012] In an optional embodiment, the carbonization temperature is 400-600℃ and the carbonization time is 1-5h; And / or, the etching step includes a gas activation treatment and an immersion in an inorganic acid solution performed sequentially.

[0013] In an optional embodiment, the gas activation treatment is carried out at a temperature of 500-1100°C for a time of 0.5-12 hours. And / or, the gas used in the gas activation treatment is selected from at least one of water vapor or carbon dioxide; And / or, the equipment used for the gas activation treatment is at least one of CVD fluidized bed or CVD rotary furnace; And / or, the mass percentage concentration of the inorganic acid solution is 10%-40%; And / or, the soaking time in inorganic acid solution is 1-6 hours; And / or, the inorganic acid in the inorganic acid solution is selected from at least one of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, carbonic acid, bromic acid, hydrocyanic acid, hydrofluoric acid and hydrobromic acid; And / or, the sintering temperature is 800-900℃, the sintering time is 1-3h, and the atmosphere is an inert atmosphere; And / or, the passivation temperature is 500-1000℃, the passivation time is 1-6℃, and the atmosphere is an inert atmosphere; And / or, the mass percentage of the highly conductive material in the mixture is 0.3%-0.7%.

[0014] Thirdly, the present invention provides a silicon-carbon material, including the porous carbon material described in any one of the foregoing embodiments or the porous carbon material prepared by the method described in any one of the foregoing embodiments.

[0015] Fourthly, the present invention provides a secondary battery comprising the silicon-carbon material described in the foregoing embodiments.

[0016] The present invention has the following beneficial effects: In this application, the first lithium salt in the porous carbon material core fills the pores of the carbon framework, providing a pre-stored lithium source to compensate for the active lithium consumed during SEI film formation during the first charge of the battery, thus mitigating initial efficiency loss. Its presence also regulates pore wettability and ion transport pathways. The nitrogen-containing compounds in the conductive layer enhance the nucleation induction ability for subsequent CVD silicon deposition, while also improving the intrinsic electronic conductivity of the conductive layer. Therefore, the porous carbon material in this application achieves a balance between cycle performance and capacity. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 A flowchart of the method for preparing porous carbon materials provided by the present invention; Figure 2 This is a scanning electron microscope image of the porous carbon material prepared in Example 1. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0020] This invention provides a porous carbon material, comprising core particles and a conductive layer located on the surface of the core particles; The core particles comprise a carbon skeleton with a porous structure and a first lithium salt and / or decomposition products of the first lithium salt filling the porous structure. The conductive layer contains nitrogen-containing compounds and / or decomposition products of nitrogen-containing compounds, wherein the nitrogen-containing compounds include at least one of ammonium phosphate compounds and organic nitrogen compounds.

[0021] In this application, the first lithium salt and / or its decomposition products fill the pores of the carbon framework in the porous carbon material core, providing a pre-stored lithium source. This compensates for the active lithium consumed during SEI film formation during the first charge of the battery, mitigating initial efficiency loss. Its presence also regulates pore wettability and ion transport pathways. Nitrogen-containing compounds in the conductive layer enhance the nucleation induction ability for subsequent CVD silicon deposition, while also improving the intrinsic electronic conductivity of the conductive layer. Therefore, the porous carbon material in this application achieves a balance between cycle performance and capacity.

[0022] The nitrogen-containing compounds and / or their decomposition products in the conductive layer can interact with the first lithium salt and / or its decomposition products filled within the carbon framework, simultaneously improving ionic and electronic conductivity, thereby enhancing the initial coulombic efficiency of the silicon-carbon anode material and reducing internal resistance. In an optional embodiment, the first lithium salt is selected from at least one of lithium hydroxide, lithium carbonate, lithium niobate, lithium oxalate, lithium chloride, lithium fluoride, lithium hydride, lithium nitride, lithium nitrate, and lithium aluminate; this is beneficial for improving the initial coulombic efficiency and long cycle life of the silicon-carbon anode material.

[0023] And / or, the mass ratio of lithium element to carbon skeleton in the first lithium salt is 0.1%~3%; this ensures both the high porosity of the porous carbon material and improves the capacity and initial coulombic efficiency of the silicon-carbon anode material. If the first lithium salt filling amount is too high, it will lead to a decrease in the pore volume in the porous carbon skeleton, a decrease in the amount of nano-silicon filling, and a decrease in the capacity of the silicon-carbon anode material; if the first lithium salt filling amount is too low, the initial efficiency of the silicon-carbon anode material will be low. In some specific embodiments, the mass ratio of lithium element to carbon skeleton in the first lithium salt in the core is 0.1%, 0.5%, 1%, 2%, etc.

[0024] And / or, the nitrogen-containing compound is selected from at least one of melamine, triammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate; these nitrogen-containing compounds can release highly electronegative groups, which interact with carbon defects, increasing the nucleation sites of nano-silicon, improving the loading and uniformity of nano-noble particles, and inhibiting silicon agglomeration and volume expansion. Simultaneously, the incorporation of N / P atoms into the carbon framework, with nitrogen providing electrons to increase carrier concentration and phosphorus widening the interlayer spacing to enhance conductive pathways, can improve overall electronic conductivity and enhance the cycling performance of the material.

[0025] And / or, the mass ratio of nitrogen element in the nitrogen-containing compound to the mass of the core particle is 0.001%-0.005%; And / or, the carbon skeleton is coconut shell pyrolysis carbon; coconut shell pyrolysis carbon has high mechanical strength and can significantly suppress the volume expansion of nano-silicon particles.

[0026] And / or, the carbon skeleton is a carbon material with a disordered structure; And / or, the carbon skeleton has a hierarchical pore distribution; the hierarchical pore structure not only reserves space for the volume expansion of the nano-silicon particles during the charging and discharging process, but also facilitates the filling of the first lithium salt therein, thereby improving the capacity and cycle performance of the silicon-carbon anode material.

[0027] And / or, the thickness of the conductive layer is 50-100 nm; this facilitates the coating and modification of the carbon skeleton surface, while limiting the volume expansion of the nano-silicon particles in the silicon-carbon material prepared therefrom during charge and discharge, improving the cycle life of the silicon-carbon anode material, and reducing the contact activity between the carbon skeleton surface and the electrolyte, effectively suppressing the occurrence of side reactions. A conductive layer thickness of 50-100 nm ensures the effective coating and modification of the carbon skeleton surface, and also improves the conductivity of the porous carbon material. If the conductive layer thickness is too low, the improvement effect on the conductivity of the porous carbon skeleton material will be poor; if the conductive layer thickness is too high, it will reduce the content of nano-silicon particles in the porous carbon material, thereby reducing the specific capacity of the silicon-carbon anode material and increasing the solid-phase impedance of the silicon-carbon anode material. In some specific embodiments, the thickness of the conductive layer can be 50-60 nm, 60-70 nm, 70-80 nm, 80-90 nm, 90-100 nm, etc.

[0028] And / or, the conductive layer includes a highly conductive material selected from at least one of pitch carbon, mesophase carbon microspheres, soft carbon, hard carbon, petroleum coke, carbon fiber, resin pyrolysis carbon, acetone pyrolysis carbon, alkane pyrolysis carbon, olefin pyrolysis carbon, and acetylene pyrolysis carbon. These materials have high conductivity, which can further improve the conductivity of the porous carbon skeleton, reduce the polarization of the silicon-carbon anode material during charge and discharge, reduce the interfacial impedance between the silicon-carbon anode material and the electrolyte, alleviate the volume expansion of the porous carbon core material, and improve the cycle performance and rate performance of the silicon-carbon anode material. At the same time, these highly conductive materials mix better with nitrogen-containing compounds and other components in the conductive layer, making it easier to form a stable conductive layer on the surface of the core particles.

[0029] And / or, the conductive layer further includes a conductive agent and / or a second lithium salt. Adding a conductive agent to the conductive layer can further improve the conductivity of the porous carbon material, reduce impedance, and extend battery life. The conductive layer stably coats the outer surface of the core carbon material skeleton, and the lithium salt can act as a pre-lithiation agent, reducing the consumption of lithium ions by the solid electrolyte film formed on the surface of the nano-silicon-carbon composite material during the first charge-discharge process, thereby improving the first coulombic efficiency of the nano-silicon-carbon composite material.

[0030] In an optional embodiment, the mass ratio of the highly conductive material to the nitrogen element in the nitrogen-containing compound in the conductive layer is 1:0.1-0.4; And / or, in the conductive layer, the mass ratio of highly conductive material to conductive agent is 1:0.5-0.7; And / or, in the conductive layer, the mass ratio of the highly conductive material to the lithium element derived from the second lithium salt is 1:0.1-0.5; The above-mentioned ratio of the conductive layer helps to further suppress the volume expansion of silicon-carbon materials during charge-discharge cycles, extend the battery's lifespan, and provide conductivity while reducing the overall impedance of the particles. In addition, the presence of nitrogen-containing compounds can increase the deposition sites of nano-silicon particles, which is beneficial to increasing the content of nano-silicon in silicon-carbon materials and improving capacity. Furthermore, the use of a second lithium salt for pre-lithiation further compensates for the consumption of lithium ions by the formation of the solid electrolyte membrane during the first charge-discharge process, thereby improving the first coulombic efficiency.

[0031] And / or, the conductive agent is selected from at least one of conductive carbon black, superconducting carbon, Ketjen black, carbon nanotubes, graphene and acetylene black; these materials have high conductivity and can effectively improve the electron transport efficiency in porous carbon materials.

[0032] And / or, the second lithium salt is selected from at least one of lithium bis(trifluoromethyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium carbonate, lithium hydroxide, lithium fluoride, and lithium hydride. These lithium salts can form "pre-intercalation" sites to compensate for the active lithium consumed in the formation of the SEI film during the first charge of the battery, reducing irreversible capacity loss.

[0033] In an optional embodiment, the micropore volume in the carbon framework accounts for 35% to 90% of the total pore volume. High micropore content provides excellent adsorption for nano-silicon, facilitating the deposition of nano-silicon particles within and on the surface of the porous carbon material. This, in turn, improves the capacity of the silicon-carbon anode material and reduces the volume expansion of nano-silicon particles during battery charging and discharging. The presence of mesopores and macropores provides effective storage space and ion pathways for nano-silicon particles. The carbon framework of this application, through a suitable multi-level distribution of micropores and mesopores, further promotes the filling and adsorption of nano-silicon particles within the porous carbon framework, thereby improving the cycle life and high capacity retention of the silicon-carbon anode material.

[0034] And / or, the total pore volume of the carbon framework is 0.85 cc / g to 1.2 cc / g; this allows the porous carbon material sufficient volume expansion buffer space, while providing effective active sites required for the deposition of nano-silicon particles, increasing the silicon content in the nano-silicon-carbon composite material, effectively ensuring the silicon-carbon anode material has a high capacity, thus achieving a balance between high capacity and long cycle life. The total pore volume of the carbon framework can be 0.85 cc / g to 0.90 cc / g, 0.90 cc / g to 1.0 cc / g, 1.0 cc / g to 1.2 cc / g, etc.

[0035] And / or, the carbon skeleton particle size D50 is 3-15 μm. The D50 of the carbon skeleton not only affects the expansion rate of the silicon-carbon anode material, but also its initial coulombic efficiency and the compaction density of the anode sheet. A carbon skeleton of this particle size has higher support strength, further limiting the volume expansion of the nano-silicon particles during charge-discharge cycles, and also helps improve the coating effect of the silicon-carbon anode material and the compaction density of the anode sheet. If the D50 of the carbon skeleton is less than 3 μm, the overall particle size of the silicon-carbon anode material prepared by CVD deposition is small, and powder will appear during the preparation of the anode slurry, affecting the coating quality and the compaction density of the anode sheet. It will also cause the specific surface area of ​​the silicon-carbon anode material to be too large, resulting in excessive consumption of electrolyte to form an SEI film and reducing the initial efficiency of the silicon-carbon anode material. If the D50 of the carbon skeleton is too large, it will also affect the coating and compaction density of the anode sheet. In some specific embodiments, the D50 of the carbon skeleton can be 3-5 μm, 5-10 μm, 10-15 μm, etc.

[0036] The present invention also provides a method for preparing the porous carbon material described in any one of the foregoing embodiments, the process of which is as follows: Figure 1 As shown, it includes: The first lithium salt is filled into the pores of the carbon framework to obtain the core particles; The core particles are coated with a mixture of highly conductive materials and nitrogen-containing compounds, and then the resulting coating material is passivated to obtain the porous carbon material.

[0037] The method for preparing porous carbon materials in this application is simple, suitable for large-scale industrial production and application, and the prepared porous carbon materials have high structural strength, high ionic conductivity, low impedance, and good cycle stability.

[0038] In an optional embodiment, the preparation of a carbon skeleton is also included: the biomass powder is sequentially carbonized and etched to obtain the carbon skeleton; the carbon skeleton has a disordered structure.

[0039] And / or, the filling of the first lithium salt includes uniformly mixing the first lithium salt with a carbon skeleton and then sintering it to obtain the core particles; And / or, coating includes uniformly mixing the mixture with the core particles, followed by passivation; And / or, the mixture further includes a conductive agent and / or a second lithium salt; And / or, the biomass is selected from at least one of tall coconut shells, dwarf coconut shells, and hybrid coconut shells.

[0040] In an optional embodiment, the carbonization temperature is 400-600℃ and the carbonization time is 1-5h; And / or, the etching step includes sequential gas activation treatment and immersion in an inorganic acid solution. The etching of biomass powder through gas activation treatment and immersion in an inorganic acid solution forms a hierarchical porous structure in the biomass particles, resulting in a total pore volume of 0.85 cc / g to 1.2 cc / g, and creating a suitable proportion of micropores. The immersion treatment in inorganic acid can simultaneously adjust the proportion of impurity elements in the biomass, improving the stability and conductivity of the porous carbon material.

[0041] In an optional embodiment, the gas activation treatment is carried out at a temperature of 500-1100°C for a time of 0.5-12 hours. And / or, the gas used in the gas activation treatment is selected from at least one of water vapor or carbon dioxide; And / or, the equipment used for the gas activation treatment is at least one of CVD fluidized bed or CVD rotary furnace; And / or, the mass percentage concentration of the inorganic acid solution is 10%-40%; And / or, the soaking time in inorganic acid solution is 1-6 hours; And / or, the inorganic acid in the inorganic acid solution is selected from at least one of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, carbonic acid, bromic acid, hydrocyanic acid, hydrofluoric acid, and hydrobromic acid; these inorganic acids all have a good etching effect on carbonized biomass particles.

[0042] And / or, the sintering temperature is 800-900℃, the sintering time is 1-3h, and the atmosphere is an inert atmosphere, wherein the inert atmosphere is selected from at least one of nitrogen, argon and helium; And / or, the passivation temperature is 500-1000℃, the passivation time is 1-6℃, and the atmosphere is an inert atmosphere; the inert atmosphere is selected from at least one of nitrogen, argon and helium; passivation converts the highly conductive material in the conductive layer into carbon material, improving the conductivity of the negative electrode material, and at the same time, passivation treatment is conducive to a more stable bond between the conductive layer and the core particles.

[0043] It should be noted that the lithium salts and nitrogen-containing compounds in this application may decompose after high-temperature processes such as sintering and passivation, and the decomposition products may be incorporated into the core particles or conductive layer.

[0044] And / or, the mass percentage of the highly conductive material in the mixture is 0.3%-0.7%.

[0045] The present invention also provides a silicon-carbon material, including the porous carbon material described in any one of the foregoing embodiments or the porous carbon material prepared by the method described in any one of the foregoing embodiments.

[0046] The porous carbon material used in this application exhibits high structural strength, high electronic conductivity, high specific surface area, high total pore volume content, and high microporosity. This contributes to the silicon-carbon material's high capacity and initial coulombic efficiency, long cycle life, and low expansion rate during charge-discharge cycles, thus improving the overall performance of batteries using it.

[0047] This invention also provides a negative electrode sheet comprising the aforementioned silicon-carbon material. The negative electrode sheet of this application exhibits high energy density and ionic conductivity, and demonstrates good stability and low expansion rate during cyclic charging and discharging, resulting in good cycle life and safety.

[0048] In some embodiments, the negative electrode sheet also includes components such as binders and conductive agents. In some specific embodiments, the negative electrode sheet is obtained by preparing a slurry from silicon-carbon negative electrode material with binders, conductive agents, and solvents, and then coating it onto the surface of a copper current collector by means of coating or other methods, followed by baking. This invention does not specifically limit the components such as binders, conductive agents, and solvents in the negative electrode sheet; in practical applications, appropriate specific materials can be selected according to actual needs.

[0049] The present invention also provides a secondary battery comprising the silicon-carbon material described in the foregoing embodiments, which has good cycle life and safety.

[0050] In some implementations, the secondary battery can be an all-solid-state battery or other secondary lithium-ion batteries containing an electrolyte.

[0051] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0052] The test methods involved in the following embodiments and comparative examples are as follows: (1) Testing of pore diameter and total pore volume In this invention, the pore size distribution and total pore volume were tested using a BSD-660 high-performance specific surface area and pore size analyzer. The material was heated at a vacuum of 10~2 Pa and a temperature of 200℃ to remove impurities and volatiles from the pores. Then, the liquid nitrogen adsorption-desorption method was used for testing. The pore volume distribution and pore size distribution were calculated by the amount of nitrogen adsorbed and desorbed by the sample. The results were described according to the BJH method and the Kelvin equation ln(p / p0)=(2γV) / (RTr), where r is the droplet radius, R is the gas constant, T is the absolute temperature, and γ and V are the surface tension and molar volume of the liquid at that temperature, respectively.

[0053] (2) Particle size test In this invention, the particle size is tested using a Malvern-3000 laser particle size analyzer with a refractive index of 6%. This method is a wet flow particle shape analysis. By measuring the dispersion of the well-dispersed liquid through the sample chamber, high-frequency interval continuous imaging is used to photograph the material particles. Finally, the equivalent circle diameter of the particle is calculated by analyzing the image as the particle diameter. The number of diameters is counted to obtain the particle size distribution curve of different particles, and D50 is calculated.

[0054] Example 1 This embodiment provides a method for preparing coconut shell-based porous carbon materials, specifically including the following steps: S10: High-grade coconut shells were carbonized in a high-temperature box furnace at 500℃ for 3 hours to obtain porous carbon precursor particles. These particles were then activated at 950℃ for 3 hours in an activation device with a volume ratio of 8:2 water vapor and carbon dioxide. After cooling, the particles were removed and immersed in a mixed acid solution of hydrochloric acid, nitric acid, and hydrofluoric acid (15% by mass) for 2 hours (mass ratio of 15:5:1). Following washing and pulverization, a carbon framework with a multi-level porous structure and a particle size D50 of 8 μm was obtained. The total pore volume of the carbon framework was measured to be 0.95 cc / g, with micropores (pore size < 2 nm) accounting for 88% of the total pore volume. S20: After mixing the carbon skeleton with lithium fluoride, the mixture is placed in a box furnace containing nitrogen and heat-treated at 850°C for 2 hours to obtain the core particles, wherein the mass ratio of lithium element in lithium fluoride to carbon skeleton is 2%; S30: The core particles are thoroughly mixed with a slurry comprising asphalt, ammonium dihydrogen phosphate, carbon nanotubes, and lithium carbonate, and then dried to obtain the coated particles. The mixture contains 0.5% asphalt by mass, 0.1% ammonium ions derived from ammonium dihydrogen phosphate by mass, 0.3% carbon nanotubes by mass, and 0.1% lithium elements derived from lithium carbonate by mass. The mass of the mixture accounts for 5% of the mass of the core particles. After obtaining the coated particles, they are passivated at 850℃ for 2 hours to obtain coconut shell-based porous carbon material. The scanning electron microscope image is shown below. Figure 2 As shown, the thickness of the conductive layer is 80 nm.

[0055] Example 2 This embodiment provides a method for preparing coconut shell-based porous carbon material. The difference from Embodiment 1 is that lithium fluoride is replaced with lithium oxalate in step S20, and the mass ratio of lithium element to carbon skeleton in lithium oxalate is 1%.

[0056] Example 3 This embodiment provides a method for preparing a coconut shell-based porous carbon material. The difference from Embodiment 1 is that the mass of the mixture in step S30 accounts for 3% of the mass of the core particles, and the thickness of the conductive layer in the obtained coconut shell-based porous carbon material is 50 nm.

[0057] Example 4 This embodiment provides a method for preparing a coconut shell-based porous carbon material. The difference from Embodiment 1 is that the asphalt in the mixture is replaced with an equal mass of mesophase carbon microspheres, and the thickness of the conductive layer in the obtained coconut shell-based porous carbon material is 80 nm.

[0058] Example 5 This embodiment provides a method for preparing coconut shell-based porous carbon material. The difference from Example 1 is that in step S10, the activation time is extended to 4 hours to obtain a carbon skeleton with a particle size D50 of 8 μm. The total pore volume is measured to be 1.1 cc / g, and micropores account for 70% of the total pore volume.

[0059] Example 6 This embodiment provides a method for preparing a coconut shell-based porous carbon material. The difference from Embodiment 1 is that in step S30, the mass fraction of asphalt in the mixture is 0.3%, the mass fraction of ammonium ions derived from ammonium dihydrogen phosphate is 0.3%, the mass fraction of carbon nanotubes is 0.3%, and the mass fraction of lithium elements derived from lithium carbonate is 0.1%. The thickness of the conductive layer of the obtained coconut shell-based porous carbon material is 80 nm.

[0060] Example 7 This embodiment provides a method for preparing coconut shell-based porous carbon material. The difference from Embodiment 1 is that: in step S10, the tall coconut shell is replaced with the dwarf coconut shell to obtain a carbon skeleton with a particle size D50 of 8 μm; the total pore volume is measured to be 0.8 cc / g, and the micropores account for 60% of the total pore volume.

[0061] Comparative Example 1 This comparative example provides a method for preparing porous carbon materials. The difference from Example 1 is that in step S10, the activation time is shortened to 1 h, and a carbon skeleton with a particle size D50 of 8 μm is obtained. The total pore volume is measured to be 0.5 cc / g, and micropores account for 20% of the total pore volume.

[0062] Comparative Example 2 This comparative example provides a method for preparing porous carbon materials, which differs from Example 1 in that the mass ratio of lithium element to carbon skeleton in lithium fluoride in step S20 is 0.05%.

[0063] Comparative Example 3 This comparative example provides a method for preparing porous carbon materials. The difference from Example 1 is that in step S30, lithium carbonate is not added to the mixture, and the mass fraction of asphalt in the mixture is increased to 0.6%. The thickness of the conductive layer of the coconut shell-based porous carbon material is 80 nm.

[0064] Comparative Example 4 This comparative example provides a method for preparing porous carbon materials. The difference from Example 1 is that the activation temperature in step S10 is increased to 1200℃, resulting in a carbon skeleton with a particle size D50 of 20μm. The total pore volume is measured to be 1.6cc / g, and micropores account for 95% of the total pore volume.

[0065] Comparative Example 5 This comparative example provides a method for preparing porous carbon materials. The difference from Example 1 is that the mass of the mixture in step S30 accounts for 1% of the mass of the core particles, and the thickness of the conductive layer of the coconut shell-based porous carbon material is 10 nm.

[0066] Comparative Example 6 This comparative example provides a method for preparing porous carbon materials. The difference from Example 1 is that the activation temperature in step S10 is reduced to 500℃, resulting in a carbon skeleton with a particle size D50 of about 8μm. The total pore volume is measured to be 0.3cc / g, and micropores account for 15% of the total pore volume.

[0067] Comparative Example 7 This comparative example provides a method for preparing porous carbon materials. The difference from Example 1 is that in step S30, the mass fraction of asphalt in the mixture is 0.8%, the mass fraction of ammonium ions derived from ammonium dihydrogen phosphate is 0.05%, the mass fraction of carbon nanotubes is 0.05%, and the mass fraction of lithium elements derived from lithium carbonate is 0.1%, resulting in a coconut shell-based porous carbon material with a conductive layer thickness of 80 nm.

[0068] Test example: Secondary batteries were prepared and tested using the porous carbon materials prepared in the above embodiments and comparative examples, specifically including: Silicon-carbon preparation involves sequentially passing porous carbon material through silane vapor deposition and acetylene pyrolysis vapor phase carbon coating to obtain silicon-carbon anode material, wherein the silicon content is 48% and the carbon coating layer thickness is 50 nm.

[0069] In the preparation of the electrode sheet, the obtained silicon-carbon anode material, thickener sodium carboxymethyl cellulose, binder styrene-butadiene rubber and conductive agent Super-P are mixed in a weight ratio of 94.5:1.5:1.5:2.5 and prepared into a paste using pure water as a solvent. The paste is then uniformly coated onto copper foil, dried, stamped into small round sheets with a diameter of 14 mm, and then rolled into anode sheets. The silicon-carbon anode material content in the electrode sheet is 10 mg.

[0070] The secondary battery was assembled in an argon-filled glove box, where the negative electrode, a 19mm diameter polypropylene separator, a lithium metal sheet, and an electrolyte with a concentration of 1mol / L were assembled and packaged into a CR2032 coin cell. The electrolyte contained ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, and the lithium salt was LiPF6.

[0071] The charge and discharge performance was tested using the Wuhan Landian Charge and Discharge System test cabinet. The charging was performed using the constant current and constant voltage method, and the discharging was performed using the constant current method. The charge and discharge current was 0.1C, the voltage range was 0~1.5V, and the test temperature was 25℃. The specific capacity, initial efficiency, and cycle life were measured (the industry standard capacity decay was cut off when it reached 80% of the initial capacity). The test results are shown in Table 1.

[0072] Table 1

[0073] The test results above show that, compared with Example 1 and Comparative Examples 1, 4, and 6, when the total pore volume of the core of the porous carbon material is too large or too small, or when there are too many or too few micropores in the hierarchical pore structure, the specific capacity, first charge-discharge efficiency, and cycle life of the prepared secondary battery will be affected.

[0074] A comparison of Example 1 and Comparative Examples 2 and 3 shows that when the lithium salt content in the carbon skeleton and the lithium salt content in the conductive layer decreases, the specific capacity, first charge-discharge efficiency and cycle life of the battery will both decrease.

[0075] As can be seen from the comparison between Example 1 and Comparative Examples 5 and 7, when the content of nitrogen-containing compounds, the content of carbon nanotubes and the thickness of the conductive layer decrease, the specific capacity, first charge-discharge efficiency and cycle life of the battery will also decrease.

[0076] The coconut shell-based porous carbon material provided in this application features a hierarchical porous carbon framework core that not only provides space for the volume expansion of nano-silicon materials during charge and discharge but also facilitates the filling of the first lithium salt within it, thus playing a role in pre-lithiation and improving the initial efficiency and cycle life of the nano-silicon-carbon anode material prepared using this porous carbon. The nitrogen-containing compounds in the conductive layer increase the deposition sites of nano-silicon particles, enhancing the deposition amount of nano-silicon within the porous carbon framework and further improving the silicon-carbon specific capacity. Furthermore, the pre-lithiation further compensates for the lithium-ion consumption during the formation of the solid electrolyte membrane during the first charge and discharge process, improving the initial coulombic efficiency.

[0077] The method of this invention uses biomass-based coconut shells as raw materials, and obtains anode materials with better consistency through carbonization, activation and other processes. The preparation process is simple and suitable for large-scale industrial production and application. Furthermore, the porous carbon prepared by this method is further deposited with nano-silicon to form silicon-carbon anode materials with high specific capacity, high ionic conductivity, low impedance and long cycle life.

[0078] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A porous carbon material, characterized in that, It includes a core particle and a conductive layer located on the surface of the core particle; The core particles comprise a carbon skeleton with a porous structure and a first lithium salt and / or decomposition products of the first lithium salt filling the porous structure. The mass ratio of lithium element to carbon skeleton in the first lithium salt is 0.1%~3%, and the carbon skeleton is coconut shell pyrolysis carbon; The conductive layer contains nitrogen-containing compounds and / or decomposition products of nitrogen-containing compounds, wherein the nitrogen-containing compounds include at least one of ammonium phosphate compounds and organic nitrogen compounds; the mass ratio of nitrogen element from the nitrogen-containing compounds to the mass of the core particles is 0.001%-0.005%.

2. The porous carbon material according to claim 1, characterized in that, The first lithium salt is selected from at least one of lithium hydroxide, lithium carbonate, lithium niobate, lithium oxalate, lithium chloride, lithium fluoride, lithium hydride, lithium nitride, lithium nitrate, and lithium aluminate; And / or, the nitrogen-containing compound is selected from at least one of melamine, triammonium phosphate, diammonium hydrogen phosphate, and diammonium dihydrogen phosphate; And / or, the carbon skeleton is a carbon material with a disordered structure; And / or, the carbon framework has a hierarchical pore distribution; And / or, the thickness of the conductive layer is 50-100 nm; And / or, the conductive layer includes a highly conductive material selected from at least one of pitch carbon, mesophase carbon microspheres, soft carbon, hard carbon, petroleum coke, carbon fiber, resin pyrolysis carbon, acetone pyrolysis carbon, alkane pyrolysis carbon, olefin pyrolysis carbon, and acetylene pyrolysis carbon. And / or, the conductive layer further includes a conductive agent and / or a second lithium salt.

3. The porous carbon material according to claim 2, characterized in that, In the conductive layer, the mass ratio of nitrogen in the highly conductive material and the nitrogen-containing compound is 1:0.1-0.4; And / or, in the conductive layer, the mass ratio of highly conductive material to conductive agent is 1:0.5-0.7; And / or, in the conductive layer, the mass ratio of the highly conductive material to the lithium element derived from the second lithium salt is 1:0.1-0.5; And / or, the conductive agent is selected from at least one of conductive carbon black, super conductive carbon, Ketjen black, carbon nanotubes, graphene and acetylene black; And / or, the second lithium salt is selected from at least one of lithium bis(trifluoromethyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium carbonate, lithium hydroxide, lithium fluoride, and lithium hydride.

4. The porous carbon material according to claim 1, characterized in that, The micropore volume in the carbon framework accounts for 35% to 90% of the total pore volume; And / or, the total pore volume of the carbon framework is 0.85cc / g to 1.2cc / g; And / or, the particle size D50 of the carbon skeleton is 3-15 μm.

5. A method for preparing a porous carbon material according to any one of claims 1-4, characterized in that, include: The first lithium salt is filled into the pores of the carbon framework to obtain the core particles; The core particles are coated with a mixture of highly conductive materials and nitrogen-containing compounds, and then the resulting coating material is passivated to obtain the porous carbon material.

6. The method for preparing porous carbon materials according to claim 5, characterized in that, It also includes the preparation of a carbon skeleton: the biomass powder is carbonized and etched sequentially to obtain the carbon skeleton; And / or, the filling of the first lithium salt includes uniformly mixing the first lithium salt with a carbon skeleton and then sintering it to obtain the core particles; And / or, coating includes uniformly mixing the mixture with the core particles, followed by passivation; And / or, the mixture further includes a conductive agent and / or a second lithium salt; And / or, the biomass is selected from at least one of tall coconut shells, dwarf coconut shells, and hybrid coconut shells.

7. The method for preparing porous carbon materials according to claim 6, characterized in that, The carbonization temperature is 400-600℃, and the carbonization time is 1-5 hours. And / or, the etching step includes a gas activation treatment and an immersion in an inorganic acid solution performed sequentially.

8. The method for preparing porous carbon materials according to claim 7, characterized in that, The gas activation treatment temperature is 500-1100℃, and the time is 0.5-12h; And / or, the gas used in the gas activation treatment is selected from at least one of water vapor or carbon dioxide; And / or, the equipment used for the gas activation treatment is at least one of CVD fluidized bed or CVD rotary furnace; And / or, the mass percentage concentration of the inorganic acid solution is 10%-40%; And / or, the soaking time in inorganic acid solution is 1-6 hours; And / or, the inorganic acid in the inorganic acid solution is selected from at least one of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, carbonic acid, bromic acid, hydrocyanic acid, hydrofluoric acid and hydrobromic acid; And / or, the sintering temperature is 800-900℃, the sintering time is 1-3h, and the atmosphere is an inert atmosphere; And / or, the passivation temperature is 500-1000℃, the passivation time is 1-6℃, and the atmosphere is an inert atmosphere; And / or, the mass percentage of the highly conductive material in the mixture is 0.3%-0.7%.

9. A silicon-carbon material, characterized in that, The porous carbon material includes the porous carbon material according to any one of claims 1-4 or the porous carbon material prepared by the method according to any one of claims 5-8.

10. A secondary battery, characterized in that, Including the silicon-carbon material as described in claim 9.

Citation Information

Patent Citations

  • Porous carbon material as well as preparation method and application thereof

    CN114447329A

  • Pre-lithiated silicon-carbon negative electrode material, preparation method and application

    CN118825229A